Hubungan Minat dan Motivasi dengan Hasil Belajar pada Materi Proklamasi Kemerdekaan Indonesia di SMK Muhammadiyah 5 Kepanjen - Arini Sa'adah; Arif Subekti (Universitas Hamzanwadi, 2025)
Interest and motivation are important in learning. Student learning outcomes are influenced by student interest and motivation. It shows that there is a relationship between interest and motivation with student learning outcomes. The purpose of this study is to measure the extent of the relationship between student interest and motivation to learn with student learning outcomes on the material of the Proclamation of Indonesian Independence. This research uses quantitative research with survey method. The instruments used to collect data are interest and motivation questionnaires and tests in the form of 25 multiple choice questions. The sample used was students of class XI MPLB 2 SMK Muhammadiyah 5 Kepanjen which amounted to 22 students. The analysis techniques used were qualitative analysis techniques including normality test, one sample T test to see the level of interest, motivation, and student learning outcomes, correlation test, single regression test, multiple correlation test, multiple regression test, and determination calculation to test the hypothesis. The results of this study indicate that interest and motivation have a weak and insignificant positive influence on student learning outcomes. Simultaneously, interest and learning motivation have an influence on student learning outcomes by 0.07%.